PSYCHO-SOCIAL ASPECT IN THE GESTATION: THE QUESTIONAIRE OF PRENATAL EVALUATION - Armengol Asenjo, Rebeca; Chamarro Lusar, Ander; García Dié Muñoz, María Teresa (Anales de Psicología / Annals of Psychology, 2007)
This study tries to adapt and to validate questionnaire PSQ (Lederman, 1996). The questionnaire is destined to evaluate psycho-social aspects of the pregnancy to be able to study and understand better what is the “parallel mental gestation ", that could allow to be able to prevent possible conflicts and to prepare the future parents, not to the childbirth but fundamentally to be parents. The sample was composed by 291 women embarrassed with a rank of oscillating age between the 17 and 42 years. The women went to classes of preparation to the childbirth in some centers of the city of Barcelona: 101 in the Hospital of the Vall d’Hebron and the rest (190) in private centers. The results of the factorial analysis confirm six of the propose dimensions, and the coefficient α a better internal consistency. The results showed a greater acceptance of the pregnancy in the women that have his first child. Also greater preoccupation by the own well-being and of the baby was observed, also a smaller acceptance of the pregnancy in the women who attend preparatory sessions for the childbirth in private centers. They discuss the contribution of the instrument to the promotion of the im-plied psycho-social aspects in the pregnancy.